Digital management on zakat institutions: Mapping using Biblioshiny R - Silma Lafifa Sunarya; Sabiq Al Qital (Center for Islamic Economics and Development Studies [P3EI], 2022)
Purpose – This study aims to identify and map the research most relevant to developing digital technology research trends published by leading journals on digital management in zakat institutions. Methodology – The analysis focused on describing the characteristics and trends of keywords, authors, citations, and journals. The data analyzed were 25 journal publications for the last four years starting from 2019-2022, accessed online by Dimensions on June 09 2022. The methods used were descriptive statistics and bibliometric analysis with Biblioshiny, an R-based application, to generate bibliometric maps. Findings – The study found that Indonesia's covid pandemic and zakat management blockchain is the most common words in this topic. Implications – This paper focuses on the development of the Islamic world in building and contributing to the digital ecosystem in zakat institutions. Originality – This research is expected to help carry out a comprehensive study of the center, identify research gaps, and help researchers determine research development by exploring findings that can still be developed related to digital management in zakat institutions are still limited